KONSEP ADMINISTRASI PENDIDIKAN DALAM PENINGKATAN MUTU PENDIDIKAN - Titi Komala; Astuti Darmiyanti (TABYIN: JURNAL PENDIDIKAN ISLAM, 2025)
School is an educational institution that plays a crucial role in shaping students' character. Recognizing this, educational institutions need to have educators and educational staff who are suitable for their needs, so they can carry out the educational process in accordance with applicable standards. For this reason, this research aims to determine the effectiveness of implementing the concept of educational administration in improving the quality of education. This research uses the Systematic Literature Review (SLR) method, following stages and protocols to avoid bias and subjective approaches. Materials related to educational administration, such as books, articles, and other sources, are collected, analyzed, and used to draw new knowledge. The research results indicate that in order to enhance the quality of education, educational administration must be a strong and sustainable element in every educational institution. This involves effective management, wise decision-making, and continuously updated strategic plans to meet the evolving demands of education.